Konsep Preferensi Dalam Alquran: Studi Analisis Kata Khair Pada Ayat-Ayat Alquran - Muhammad Reza Fadil (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
Preference is the tendency to choose or determine something that is considered better by leaving others. This concept is found in the style of the Quran language, which is located in the verses that have the word khair in it. However, not all wordskhair contain preferences, because the wordkhair in the Quran has many meanings. But, if this wordkhair combines with other words to form the phrase dzalikum khairun lakum then it can be understood that the verse contains the concept of preference. This article will prove this hypothesis by analyzing the wordkhair especially when combined with other words to form the phrase dzalikum khairun lakum. This research was conducted with a qualitative method of library research type by approaching aspects of assessment through semantic studies. This study aims to prove the existence of the concept of preference in the Quran and find out what is the function of the phrase language styledzalikum khairun lakum so that it is mentioned repeatedly in the Quran. As a result of the findings, it was found that of the many meanings of the wordkhair in the Quran, however, if the word khair forms a phrasedzalikum khairun lakum then it is true and proven that the verse contains the concept of Allah's preference. While the function of the phrase style of language is to emphasize or affirm the command contained in the verse, the suggestion to humans to make choices about what God commands in that verse, and as a good method of communication